(untitled) (Archives of The Medicine and Case Reports, 2024)
Hemodialysis significantly impacts the quality of life (QoL) of patients with kidney failure. Identifying modifiable risk factors is crucial for targeted interventions to improve QoL. This study aimed to analyze the risk factors associated with QoL in hemodialysis patients at Besemah Pagaralam Regional Hospital, Indonesia. This single-center observational study included 150 hemodialysis patients. Sociodemographic data, clinical characteristics, laboratory parameters, and QoL (measured using the Kidney Disease Quality of Life-36 Short Form questionnaire - KDQOL-36 SF) were collected. Univariate and multivariate analyses were performed to identify independent predictors of QoL. The mean age of participants was 55.2 ± 12.3 years, with 62% being male. The mean duration of hemodialysis was 3.8 ± 2.5 years. Factors independently associated with lower QoL included older age (OR 1.04, 95% CI 1.01-1.07, p=0.01); Lower hemoglobin level (OR 0.92, 95% CI 0.87-0.97, p=0.003); Presence of comorbidities (diabetes, cardiovascular disease); Depression symptoms (OR 0.85, 95% CI 0.79-0.92, p<0.001). This study identifies several modifiable risk factors associated with impaired QoL in hemodialysis patients. Interventions targeting anemia management, comorbidity control, and mental health support may be beneficial in improving the overall well-being of these patients.